Prenatal dental practices in the city of Itacoatiara, Amazonas, from the perspective of pregnant women - Albuquerque Pereira Simões, Keline; de Araújo Passos, Shirley Maria; Silveira Pinto, Adriana Beatriz; de Arruda Regis Aranha, Lauramaris; Xavier Monteiro, Angela (O Mundo da Saúde, 2022)
This study sought to investigate the practices of prenatal dental care from the perspective of pregnant women in the city of Itacoatiara, Amazonas. An instrument composed of 14 objective questions was used, applied to 146 pregnant women, over 18 years of age, followed up in seven family health units in the city of Itacoatiara, Amazonas. The data were descriptively analyzed using absolute and relative frequencies, using the chi-squared test (p<0.05). Of the total number of participants, 49.32% reported not having gone to a dentist appointment during pregnancy, and among those who did, 47.30% went only once, and in 31.08% of the cases the appointment was made by a nursing professional. Regarding health education activities, 91.78% did not participate in any activity and 54.11% did not receive oral hygiene guidance. As the follow-up and dental care during pregnancy are essential to minimize oral changes that may affect the health of the mother and baby, the importance of strengthening actions by oral health teams in raising awareness among pregnant women about the importance of prenatal dental care is highlighted, contributing to a greater adherence to the monitoring of their oral health conditions.